Credit-less Recoveries : Neither a Rare nor an Insurmountable Challenge - Sugawara, Naotaka; Zalduendo, Juan (World Bank, Washington, DC, 2013)
This paper examines why some countries experience economic recoveries without pick-up of bank credit (credit-less) and how different this recovery pattern is from the case where credit is increased as an economy recovers (credit-with). To answer these questions, the paper uses quarterly data covering 96 countries and identifies 272 recovery episodes. It finds that more than 25 percent of all recoveries are credit-less and around 45 percent of all credit-less recoveries occurred in 2009-10. It also finds that output and investment growth tends to be lower in credit-less events but, by eight quarters after the trough date, the gap between credit-less and credit-with episodes is mostly exhausted. Results of the probit estimations show that the size of the downturn and the extent of external adjustment are associated with the likelihood of credit-less recoveries. Moreover, fiscal loosening tends to be related to credit-less events while monetary easing and a country's decision to seek an International Monetary Fund-supported program reduce the probability of credit-less recoveries. Finally, the model suggests that many countries in the Europe and Central Asia region were likely to experience credit-less recoveries following the global financial crisis in 2008/09. What is more worrisome for them is the fact that they are facing another negative external shock.